Integration of Digital Technology in English Language Learning in Elementary Schools : Trends, Challenges, and Opportunities - Retno Fentari (International Journal of Educational Technology and Society, 2025)
This study explores the integration of digital technology in English language learning in primary schools, focusing on the trends, challenges, and opportunities it presents. The primary objective is to identify the current trends in the use of digital technology in English language instruction, examine the challenges faced by educators and students in its implementation, and assess the potential opportunities for enhancing the quality of learning. A Systematic Literature Review (SLR) method was used to gather and analyze relevant studies published over the last decade. The findings reveal that digital technology has significantly impacted teaching and learning by providing broader access to educational resources and enabling more interactive, engaging, and student-centered learning experiences. However, challenges such as infrastructure limitations, access gaps, and technical skills remain barriers to effective implementation. The study also identifies key opportunities for improving teacher training, expanding access to materials, and leveraging interactive platforms to enhance English language acquisition. The implications of these findings suggest that digital technology, when appropriately integrated, can greatly improve the quality of English education in primary schools. Future research should focus on addressing the identified challenges and exploring more inclusive technological solutions.